Evaluating the Efficacy of Gene Silencing in Dopaminergic Neuronal Cells In-Vitro using Gold Nanorods (GNR) with Different Surface Properties Complexed to DARPP-32 siRNA. - Atcha Kopwitthaya; Wing Cheung Law; Lisa A Vathy; Ravikumar Aalinkeel; Jessica L. Reynolds; Bindukumar Nair; Supriya D. Mahajan (Journal of Advanced Pharmaceutical Science And Technology, 2014)
Gold nanorods (GNRs) are plasmonic nanostructures by virtue of their size-dependent optical properties, offer a bionanotechnology platform in areas of bioimaging, drug delivery etc for disease diagnosis, prognosis, and therapy. GNRs are more sensitive to changes in local environments, and offer strong scattering and absorption efficiencies thus providing opportunities to integrate multiple imaging modes and therapeutic strategies. The hydrodynamic size of these GNR under physiological condition is <100 nm, making them ideal as intracellular delivery agents. RNA interference using small inhibitory RNA (siRNA) has become a powerful tool to downregulate mRNA levels by cellular nucleases that become activated when a sequence homology between the siRNA and a respective mRNA molecule is detected. siRNA is used to silence genes involved in the pathogenesis of various diseases and holds a promising option for the development of novel therapeutic strategies in neurological dysregulation such as that observed in drug addiction. However, a major challenge in gene therapy continues to be effective delivery of siRNA and its sustained release at targeted sites. Previously, we have shown the GNR coated with poly (diallyldimethyl ammoniumchloride) (GNR-PDDAC) electrostatically complexed to the dopamine- and cAMP-regulated neuronal phosphoprotein (DARPP-32) siRNA forming a GNR-nanoplex that was able to effectively silence the DARPP-32 gene expression in dopaminergic neuronal (DAN) cell cultures in- vitro. The current report, explores if modification of the surface coating properties of the GNRs with different surface coatings namely, amino terminated polyethylene glycol (GNR-PEG), polyethyleneimine (GNR-PEI) and Chitosan (GNR-CIT) alters their stability, cytotoxicity and DARPP-32 gene silencing efficiency in-vitro dopaminergic neuronal (DAN) cell cultures with the goal of determining the most suitable surface coating for the GNR that would provide a GNR-nanoplex with the most stability, least cytotoxicity and most efficacious gene silencing.
Keywords: Gold Nanorods